Evaluation of the role of rs2227983 polymorphism of EGFR gene in the development of allergic asthma - A. B. Аveryanov; I. I. Cherkashina; S. Yu. Nikulina; E. Yu. Kuznetsova; V. N. Maksimov (Туберкулез и болезни лёгких)
The objective of the study: to study rs2227983 polymorphism of EGFR gene in patients with allergic asthma and healthy individuals.Subjects and Methods. 179 patients suffering from allergic asthma were included in the study. The diagnosis and degree of severity were established in accordance with the GINA recommendations. The Control Group included apparently healthy individuals (n = 217). Patients with allergic asthma underwent standard laboratory and instrumental examinations and DNA typing.Results. A statistically significant predominance of AG genotype frequency in the group of patients with allergic asthma, including women, versus the group of healthy individuals, was established. AG rs2227983 genotype of EGFR gene was found to be significantly more common in patients with mild and moderate allergic asthma including women, than in healthy individuals, including women.Conclusion. The association of rs2227983 polymorphism of EGFR gene with allergic asthma has been established. A homozygous GG genotype may play a protective role against the disease.